UPAYA MENINGKATKAN PRESTASI BELAJAR DIREKSI MELALUI PENGGUNAAN MULTI MEDIA TERPADU DI JURUSAN PENDIDIKAN SENI MUSIK FBS - Kun Setyaning Astuti; A. M. Susilo Pradoko; F. X. Diah K. (Imaji, 2007)
AbstractThe aims of this study are to find out an effective strategy in using integrated multimedia in the learning of directing in the Music Study Program FBS UNY as well as to reveal the influence of integrated multimedia on students' learning chievement in the Directing class in 2005. The study is based on a class action research, the sample of which is the students of the Non-regular program taking Basic Directing class. The research was carried out in three cycles. The data were collected through tests, observation, and interviews. The function of the test is to know the students' achievement while that of the observation and interviews is to identify the effective strategy in using the integrated multimedia. The analysis techniques applied are t-test, continued with Dunnet test. The result shows that the use of integrated multimedia in the learning  of directing made the learning process enjoyable, attractive, and made the lessons easy to understand. Besides, the integrated multimedia could increase the students' achievement effectively. Keywords: students' achievement, directing class, integrated multimedia